Water Pollution in Wood-Based Industries in Thailand: Case Study of a Hardboard Factory - Rachaneewan, Charoenwanying (1991)
A study of waste water characteristics from a hardboard factory was conducted in order to determine and identify the appropriateness of the waste water treatment process. The factory uses a combination of treatment processes such as the sedimentation, anaerobic and aerated process. Grab samples were used to analyse the crucial parameters of the waste water. The results show that the BOD, COD, TDS and SS values' of the discharge were 31 mg/l, 409 mg/l, 2,213 mg/l and 107 mg/l, respectively, while the average removal efficiency were 99.5, 97.5, 68.4, and 90.5 %, respectively. The raw waste water shows a high loading of 10,283 kg/day BOD, 25,623 kg/day COD, 13,380 kg/day TDS and 2,158 kg/day SS. The overall treatment system has an approximate retention time of 13 days. In addition, some properties such as colour, and odour were also observed. Generally, the results of this study indicated that the waste water from the factory was properly treated in compliance with the Thai Industrial Effluent Standards.